What the EU Can Learn from the American Experience with Unemployment Insurance - Suzanne Simonetta (Intereconomics, 2017)
This paper aims to contribute to the ongoing unemployment insurance dialogue and debate by providing an overview of the equivalent program in the US and identifying valuable lessons from the American experience.
Keywords: 330